Tricuspid valve reconstruction, a treatment option in acute endocarditis - Lange, Rüdiger; De Simone, Raffaele; Bauernschmitt, Robert; Tanzeem, Ahmed; Schmidt, C.; Hagl, Siegfried (European journal of cardio-thoracic surgery, 1996)
Tricuspid valve endocardititis is treated surgically by total valveexcision or valve replacement. Both procedures are controversial withregard to the hemodynamic consequences and to the long-term prognosis. Inthe following, results of tricuspid valve repair in acute infectiveendocarditis are reported and discussed as an additional treatment option.Between January 1988 and December 1993, 118 patients were operated on foracute valve endocarditis at our institution. Eleven of these patients hadtricuspid valve endocarditis, isolated (n = 7) or combined withendocarditis of a left-sided valve (n = 4). In the cases with isolatedtricuspid valve endocarditis, the indication for surgery was intractableinfection in six and hemodynamically relevant tricuspid insufficiency inone out of seven patients. In all patients with associated left-sidedendocarditis, the indication was hemodynamic deterioration. In eightpatients the tricuspid valve endocarditis was treated as follows:debridement, vegectomy, patch reconstruction of the cusps, reducing thecusps to two. In three patients reconstruction was not possible because ofextensive involvement of all parts of the valve, including the valve ringand the papillary muscles. In these patients primary valve replacement (n =1) or valve excision with secondary replacement (n = 2) was performed. Infour patients tricuspid reconstruction was combined with mitral (n = 1),aortic (n = 1) or double valve replacement (n = 2). Postoperatively, signsof infection vanished in all surviving patients (n = 10) and tricuspidvalve endocarditis healed without recurrences. Implanted prostheticmaterial did not lead to recurrent infection. One patient died earlypostoperatively after valve excision, in septic shock and multi-organfailure. In seven patients late echocardiographic follow-up showedtricuspid regurgitation grade 0 in three patients, I in two, II in one andIII in one. Our results suggest that valve repair is a reasonable treatmentoption for tricuspid valve endocarditis in all cases with localizedinfection of the valve. Only if extensive valve destruction excludes valverepair, would we now favor primary valve replacement over simplevalvulectomy. In all other cases primary valve reconstruction is thetreatment of choice for tricuspid valve endocarditis, if surgery isindicated.
Gesehen am 16.06.2025